THE INFLUENCE DEEP BREATH AND INTRADIALYTIC EXERCISE ON BLOOD PRESSURE IN HEMODIALYSIS PATIENTS - Aisyah (Keperawatan Anestesiologi Program Sarjana Terapan, 2024)
Background: Hemodialysis has several complications caused by kidney failure itself and because of the process during hemodialysis. Prevention of hemodialysis complications is done in various ways including deep breathing and intradialytic exercise. The aim of this study is to explain the effect of deep breath and intradialytic exercise on blood pressure in hemodialysis patients.Methods: using the quasy experiment method with the pre test and post test control group design. The population of the study in this study were hemodialysis patients who were in the hospital of dr. Sayidiman Magetan. The sample technique uses purposive sampling. The sample consisted of 30 respondents, each group consisting of 15 respondents.Results: Deep breathing and intradialytic exercise can have a significant effect on decreasing levels of decreasing systolic blood pressure (p = 0.031), and decreasing diastolic blood pressure (p = 0.013).Conclusion: 15 times breathing and 20 minutes of intradialytic exercise in 2 sessions per week for 4 weeks (each carried out HD) can affect the level of increase the value of systolic and diastolic blood pressure in hemodialysis patients